Analysis of the level of agricultural development in the Stavropol Territory and the main directions of its improvement - P. A. Chadalova; E. A. Astakhova; E. I. Krivokora; A. Yu. Kalnaya (Вестник Северо-Кавказского федерального университета)
Introduction. Agriculture, despite its strategic role in the economy, is characterized by a number of problems, the features of which largely depend on the speciﬁcs and conditions of a particular territory both at the state level and at the level of a particular region. In this regard, it is relevant to conduct a qualitative analysis of the state of agriculture and implement measures aimed at solving the identiﬁed problems.Goal. To analyze the level of agricultural development in the Stavropol Territory in the context of municipal and urban districts, to determine the directions of its improvement, to formulate the expected results.Materials and methods. The study is based on a statistical analysis of the indicators of agricultural development in the region using the method of comparison and formal logic.Results and discussion. As a result of the analysis, ratings of municipal and urban districts of the Stavropol Territory were compiled for the production of gross agricultural output in the region, in terms of crop production and livestock production, leader territories and outsider territories were identiﬁed, industry problems were identiﬁed and directions for their solution were determined by stimulating the development of small business and the creation of an agricultural educational cluster of university type in the region.Conclusion. Based on the results of the study, it can be concluded that the proposed measures will improve the level of agricultural development and, as a result, increase the level of socio-economic development of the region. The creation of a university-type agricultural educational cluster will allow for an eﬀect on four levels: for students, for educational organizations, for partner enterprises and for the region.